PPP-RTK by means of S-system theory: Australian network and user demonstration. Issue 1 (2nd January 2017) - Odijk, Dennis; Khodabandeh, Amir; Nadarajah, Nandakumaran; Choudhury, Mazher; Zhang, Baocheng; Li, Wei; Teunissen, Peter J. G.
Abstract: The development of an Australian PPP-RTK processing platform is an important component of a multi-GNSS (global navigation satellite system) enabled national positioning infrastructure. The PPP-RTK concept extends the precise point positioning (PPP) concept by providing single-receiver users with information enabling integer ambiguity resolution, thereby reducing convergence times as compared to that of PPP. In this contribution we present and discuss the underlying principles of the PPP-RTK platform for both network and user. We demonstrate its GPS-based performance and provide an outlook for when multi-GNSS constellations, such as BDS, Galileo and QZSS, become fully operational.